Interest rate policy and supply-side adjustment dynamics - Daniel Kienzler; Kai Schmid (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
In contrast to the present consensus view of stabilization policy, theoretical and empirical research strongly support the consideration of supply-side adjustment to pronounced variations of factor-utilization in order to trace a more realistic pattern of macroeconomic adjustment dynamics within simulation studies. Against this background, our paper seeks to illuminate the relevance of endogenous supply-side adjustment for monetary policy research. We modify a basic New Keynesian model by explicitly considering demand-side stimulus on the evolution of productive capacity and analyze stability, impulse response, and welfare issues if the central bank follows a simple monetary policy rule. Thereby, we control for the robustness of our policy implications by various states of output gap mismeasurement the central bank might be confronted with. We find that, in contrast to a basic New Keynesian Model, output gap stabilization plays a more prominent role when potential output is endogenous.
Keywords: E32; E50; E52; 330; Monetary policy; factor-utilization; endogenous potential output; output gap mismeasurement; Zinspolitik; Regelgebundene Politik; Konjunkturpolitik; Neukeynesianische Makroökonomik; Gesamtwirtschaftliche Produktionstheorie